Preparation method of lithium silicon alloy nanoparticles and dry process lithium silicon alloy negative electrode material

By carrying out polymer layer coating and stabilizer reaction on lithium silicon alloy nanoparticles, dry lithium silicon alloy negative electrode material is prepared, which solves the problems of time-consuming and environmental pollution in the preparation of lithium silicon alloy materials in traditional methods, and achieves high Stability and high specific capacity of lithium-ion battery negative electrode.

CN115763771BActive Publication Date: 2025-01-03UNIV OF MACAU

Patent Information

Application Number
CN202310018056.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2025-01-03
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

The preparation method of traditional lithium silicon alloy negative electrode materials is time-consuming and labor-intensive, poor economical, and has hidden dangers of environmental pollution. Moreover, lithium silicon alloys are prone to react with water and oxygen in the air, resulting in low battery performance.

Method used

The lithium silicon alloy nanoparticles are coated through a polymer layer, combined with binder, additive additive and conductive agent for dry mixing, and added stabilizer to form lithium oxygen bonds to prevent lithium loss, and prepare a high-stability dry lithium silicon alloy Negative electrode material.

Benefits of technology

It improves the stability of lithium silicon alloy particles, reduces the cost of equipment investment, avoids the reaction of lithium silicon alloy with air, and improves battery performance and specific capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115763771B_ABST
    Figure CN115763771B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a lithium-silicon alloy nanoparticle and a dry-process lithium-silicon alloy negative electrode material. The lithium-silicon alloy nanoparticle comprises a lithium-silicon alloy core and a polymer layer located on the surface of the lithium-silicon alloy core, wherein the polymer layer completely covers the lithium-silicon alloy core. By fully covering the silicon-lithium alloy core with a polymer, the stability of the lithium-silicon alloy particles can be improved, the equipment investment cost can be reduced, and the economy can be improved. Moreover, when the silicon-lithium alloy particles are used with other raw materials such as a conductive agent to prepare a negative electrode material, the reaction between the silicon-lithium alloy core inside the silicon-lithium alloy particles and water and oxygen in the external air can be effectively avoided, thereby reducing lithium loss. In addition, adding a stabilizer during the mixing process of preparing a dry-process lithium-silicon alloy negative electrode material can supplement the polymer-free vacancies that appear after the surface coating layer of the silicon-lithium alloy particles is worn, further preventing the reaction between the internal silicon-lithium alloy and the external air, reducing lithium loss, and thus improving material performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a method for preparing lithium-silicon alloy nanoparticles and a dry-process lithium-silicon alloy negative electrode material. Background Art

[0002] In recent years, with the continuous increase in the range of electric vehicles and the rapid evolution of lightweight and miniaturized electronic devices, traditional graphite anodes can no longer meet the needs of various high-capacity application scenarios. Silicon, with its 4200mAh·g -1 The theoretical specific capacity (more than ten times that of graphite negative electrode) has become an emerging hotspot in the field of negative electrode material research. However, due to the irreversible reaction during the charge and discharge cycle, part of the lithium cannot be deintercalated and forms "dead lithium", which in turn causes the battery's initial coulombic efficiency and energy density to be low, affecting battery performance. As a new type of pre-lithiation negative electrode material, lithium-silicon alloy can greatly improve the battery's initial efficiency and energy density by replenishing lithium from the negative electrode itself, and has extremely high practical application value.

[0003] At present, the preparation method of negative electrode of lithium-ion battery mainly adopts wet mixing of active materials and then coating to current collector for forming. Conventional method for manufacturing lithium silicon alloy negative electrode requires large-scale drying equipment, which is time-consuming and labor-intensive, has poor economic efficiency and has the potential of environmental pollution. During the mixing process, lithium silicon alloy easily reacts with water and oxygen in the air, resulting in loss of active materials and attenuation of electrode specific capacity. At the same time, the active material layer is coated on copper foil and aluminum foil, the battery mass is large, the energy density is low, and high-performance applications are limited. Therefore, how to obtain a dry lithium silicon alloy negative electrode with high stability, low lithium loss and high specific capacity has become one of the urgent needs in this field.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing lithium-silicon alloy nanoparticles and a dry-process lithium-silicon alloy negative electrode material to improve the above-mentioned technical problems.

[0006] The present invention is achieved in that:

[0007] In a first aspect, the present invention provides a lithium-silicon alloy nanoparticle, comprising a lithium-silicon alloy core and a polymer layer located on the surface of the lithium-silicon alloy core, wherein the polymer layer completely covers the lithium-silicon alloy core.

[0008] In a second aspect, the present invention also provides a method for preparing the above-mentioned lithium-silicon alloy nanoparticles, which comprises: generating the polymer layer by in-situ reaction on the surface of the lithium-silicon alloy core.

[0009] Optionally, the in-situ reaction to generate the polymer layer includes: performing a first polymerization coating on the lithium-silicon alloy core using a primary polymerization agent, and then performing a second polymerization coating on the lithium-silicon alloy core using a secondary polymerization agent.

[0010] In a third aspect, the present invention also provides the use of the above-mentioned lithium-silicon alloy nanoparticles in the preparation of a dry-process lithium-silicon alloy negative electrode.

[0011] In a fourth aspect, the present invention further provides a method for preparing a dry-process lithium-silicon alloy negative electrode material, comprising: fully mixing the lithium-silicon alloy nanoparticles, a binder, an additive, a conductive agent, and a stabilizer;

[0012] The stabilizer is a substance that can react on the surface of lithium-silicon alloy nanoparticles to form lithium-oxygen bonds.

[0013] In a fifth aspect, the present invention further provides a lithium-ion battery, which includes a negative electrode prepared by the above-mentioned dry-process lithium-silicon alloy negative electrode material.

[0014] The present invention has the following beneficial effects: by fully coating the silicon-lithium alloy core with a polymer, the stability of the lithium-silicon alloy particles can be improved, the equipment investment cost can be reduced, and the economy can be improved. And when the silicon-lithium alloy particles are used with other raw materials such as a conductive agent to prepare negative electrode materials, the silicon-lithium alloy core inside the silicon-lithium alloy particles can effectively avoid the reaction between the silicon-lithium alloy core inside the silicon-lithium alloy particles and the water and oxygen in the external air, thereby reducing lithium loss. In addition, adding a stabilizer during the mixing process of preparing dry-process lithium-silicon alloy negative electrode materials can supplement the polymer-free vacancies that appear after the surface coating layer of the silicon-lithium alloy particles is worn, further preventing the reaction between the internal silicon-lithium alloy and the external air, reducing lithium loss, and thus improving material performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0016] Figure 1 The process flow chart of preparing a dry lithium-silicon alloy negative electrode of the present invention;

[0017] Figure 2 It is a schematic diagram of nano-crystallization of lithium-silicon alloy in the preparation method of dry-process lithium-silicon alloy negative electrode of the present invention;

[0018] Figure 3 It is a schematic diagram of the primary modification of the lithium silicon alloy core in the preparation method of the dry process lithium silicon alloy negative electrode of the present invention;

[0019] Figure 4 It is a schematic diagram of secondary modification of the lithium-silicon alloy core in the preparation method of the dry-process lithium-silicon alloy negative electrode of the present invention;

[0020] Figure 5 The present invention is a schematic diagram of low lithium loss mixing of active materials in the preparation method of dry lithium-silicon alloy negative electrode of the present invention;

[0021] Figure 6 It is a schematic diagram of rolling low lithium loss active material in the preparation method of dry lithium silicon alloy negative electrode of the present invention;

[0022] Figure 7 It is a schematic diagram of high temperature evaporation of a low lithium loss active material layer in the preparation method of a dry lithium silicon alloy negative electrode of the present invention;

[0023] Figure 8 This is a scanning electron microscope image of fully coated lithium silicon alloy nanoparticles after secondary modification in the preparation method of the dry process lithium silicon alloy negative electrode of the present invention;

[0024] Fig. 9 This is a scanning electron microscope image of the lithium-silicon alloy core in Comparative Example 1 that has not been surface modified.

[0025] Figure numbers: 1-lithium silicon alloy powder; 2-ball mill; 3-lithium silicon alloy core; 4-primary polymerization agent; 5-solvent; 6-photoinitiator; 7-primary coated lithium silicon alloy nanoparticles; 8-secondary polymerization agent; 9-lithium silicon alloy nanoparticles; 10-mixer; 11-binder; 12-additive; 13-conductive agent; 14-stabilizer; 15-low lithium loss active material; 16-roller press; 17-low lithium loss active material layer; 18-evaporation machine; 19-target material; 20-dry lithium silicon alloy negative electrode. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0027] The following is a detailed description of the preparation method of lithium-silicon alloy nanoparticles and dry-process lithium-silicon alloy negative electrode materials provided by the invention.

[0028] First, some embodiments of the present invention provide a lithium-silicon alloy nanoparticle, which includes a lithium-silicon alloy core and a polymer layer located on the surface of the lithium-silicon alloy core, and the polymer layer completely covers the lithium-silicon alloy core.

[0029] By coating and modifying the surface of the lithium-silicon alloy core with a polymer layer, the stability of the lithium-silicon alloy particles is improved, so that the polymer layer can block the air during transportation, storage, and the subsequent mixing process to prepare negative electrode materials, thereby preventing the internal lithium-silicon alloy core from reacting with water and oxygen in the air and causing lithium loss.

[0030] Specifically, the chemical formula of the lithium silicon alloy core can be Li x Si y , wherein x:y is 1:1 to 6:1. For example, it can be selected from LiSi, Li3Si2, Li 12 Si7, Li2Si, Li7Si3, Li5Si 12 、Li3Si、Li 13 Si4、Li 21 Si5、Li 22 One or more of Si5, Li5Si or Li6Si.

[0031] In some embodiments, in order to ensure that the lithium silicon alloy core can meet the requirements of subsequent mixing to prepare negative electrode active materials after coating, the particle size of the lithium silicon alloy core can be 100nm~1000nm, for example, it can also be selected from 100nm~500nm, etc., and the better the uniformity of the particle size, the better.

[0032] It should be noted that the type of polymer layer is not limited, as long as the lithium-silicon alloy core is fully coated. Preferably, the polymer is formed by in-situ polymerization on the surface of the lithium-silicon alloy core.

[0033] Specifically, in some embodiments of the present invention, the components of the polymer layer include polyester compounds and polyethylene glycol compounds, wherein the polyester compounds and the polyethylene glycol compounds can be formed by coating the surface of the lithium silicon alloy core twice, respectively.

[0034] Secondly, some embodiments of the present invention also provide a method for preparing the above-mentioned lithium-silicon alloy nanoparticles, which comprises: generating a polymer layer by in-situ reaction on the surface of the lithium-silicon alloy core.

[0035] Specifically, see Appendix Figure 1 , the in-situ reaction to generate the polymer layer includes surface modification and secondary polymerization coating:

[0036] S1. Ball milling the lithium silicon alloy powder to prepare a lithium silicon alloy core.

[0037] Specifically, at normal room temperature (5-30°C), lithium silicon alloy powder is added to a ball mill and ground at a rotation speed of 200-650rpm to obtain a lithium silicon alloy core, wherein the lithium silicon alloy powder has a particle size of 100μm-500μm, for example, 5-200μm.

[0038] S2, the lithium silicon alloy core is polymerized and coated for the first time by a primary polymerization agent. The primary polymerization agent is a perfluorinated polymer with an average molecular weight greater than 5000. The network structure coating layer formed on the surface of the lithium silicon alloy core has nanopores and cannot form a dense and uniform coating layer.

[0039] Specifically, in some embodiments, the first polymerization coating is ultraviolet light reaction polymerization initiated by a photoinitiator.

[0040] More specifically, in some embodiments, subjecting the lithium silicon alloy core to a first polymerization coating with a primary polymerization agent comprises: placing the lithium silicon alloy core in a mixed solution having a primary polymerization agent and a photoinitiator, and reacting by ultraviolet light irradiation.

[0041] In some embodiments, the first polymerization coating time is at least 8 minutes, preferably, at least 10 minutes, and illustratively, 10 minutes can be selected.

[0042] In some embodiments, in order to better coat the lithium silicon alloy core, the mass ratio of the lithium silicon alloy core, the primary polymerization agent, the photoinitiator and the solvent is (4.4-15): (0.1-2): (0.5-3): (80-95).

[0043] In some embodiments, the primary polymerization agent includes but is not limited to at least one of perfluoropolymers containing acrylate or methacrylate groups. The photoinitiator used for the primary polymerization coating includes but is not limited to one or more combinations of diphenylacetone, α-hydroxyalkylphenone, bisbenzoylphenylphosphine oxide and benzophenone. The solvent used includes but is not limited to one or more combinations of tetrahydrofuran, N-methylpyrrolidone and cyclohexane.

[0044] S3. Perform a second polymerization coating by a secondary polymerization agent. The secondary polymerization agent is a small molecule polymer (polyethylene glycol containing acrylate or methacrylate groups with an average molecular weight of 400 to 800), which can undergo a secondary polymerization reaction with the acrylate or methacrylate groups of the primary polymerization agent, and can also self-polymerize in the area of ​​the lithium silicon alloy that is not coated by the high molecular primary polymer, thereby filling the nanopores existing in the primary polymerization coating layer on the surface of the lithium silicon alloy, forming a cross-linked, dense, and uniform external coating network structure.

[0045] Specifically, in some embodiments, the second polymerization coating is also ultraviolet light reaction polymerization initiated by a photoinitiator.

[0046] More specifically, in some embodiments, the second polymerization coating using a secondary polymerization agent includes: placing the first-coated lithium silicon alloy nanoparticles that have undergone the first polymerization coating into a mixed solution having a secondary polymerization agent and a photoinitiator, and reacting by ultraviolet light irradiation.

[0047] In some embodiments, the second polymerization coating time is at least 8 minutes, preferably, at least 10 minutes, and illustratively, 10 minutes can be selected.

[0048] In some embodiments, in order to achieve a better coating effect by the secondary polymerization coating, the mass ratio of the primary coated lithium silicon alloy nanoparticles, the secondary polymerization agent, the photoinitiator and the solvent after the first polymerization coating is (4.3-15): (0.2-2): (0.5-3): (80-95).

[0049] In some embodiments, the secondary polymerization agent includes, but is not limited to, polyethylene glycol containing acrylate or methacrylate groups with an average molecular weight of 400 to 800. The photoinitiator used in the second polymerization coating includes, but is not limited to, one or more of diphenylacetophenone, α-hydroxyalkyl phenone, bisbenzoylphenylphosphine oxide, and benzophenone. The solvent used includes, but is not limited to, one or more of tetrahydrofuran, N-methylpyrrolidone, and cyclohexane.

[0050] Some embodiments of the present invention also provide the use of the lithium-silicon alloy nanoparticles in the above embodiments in preparing a dry-process lithium-silicon alloy negative electrode.

[0051] Specifically, see again Figure 1 Some embodiments of the present invention also provide a method for preparing a dry-process lithium-silicon alloy negative electrode material, which includes: low lithium loss mixing and high specific capacity evaporation.

[0052] Specifically, in some implementations, the steps include:

[0053] S4. Fully mix the lithium silicon alloy nanoparticles, the binder, the additive, the conductive agent and the stabilizer to obtain a low lithium loss active material.

[0054] Specifically, in some embodiments, lithium silicon alloy nanoparticles, a binder, an additive, a conductive agent, and a stabilizer are placed in a mixer and fully mixed at a rotation speed of 150 rpm to 450 rpm.

[0055] The lithium-silicon alloy nanoparticles are the lithium-silicon alloy nanoparticles in any of the above embodiments, and the stabilizer is a substance that can form lithium-oxygen bonds on the surface of the lithium-silicon alloy nanoparticles.

[0056] In some embodiments, the mass ratio of lithium silicon alloy nanoparticles, binder, additive, conductive agent and stabilizer is: (30-95): (1-35): (1-15): (1-5): (2-15).

[0057] In some embodiments, the stabilizer includes but is not limited to polyethylene glycol. During the mixing process, under the action of mechanical shear force, the secondary coating structure on the surface of the lithium-silicon alloy nanoparticles is easily peeled off, so that the internal lithium-silicon alloy active material is exposed to the air. Adding the polyethylene glycol stabilizer can react to generate lithium-oxygen bonds in the area where the coating layer on the surface of the lithium-silicon alloy falls off, further filling the coating layer.

[0058] In some embodiments, the binder includes but is not limited to one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyethylene oxide, sodium hydroxymethyl cellulose, styrene-butadiene rubber, polyethylene, polypropylene and polyacrylonitrile. The additive includes but is not limited to one or more of polypropylene carbonate, polytrimethylene carbonate and polycyclohexene carbonate; the conductive agent includes but is not limited to one or more of composite conductive agent SP, carbon nanotubes, nanocarbon fibers, Ketjen black and conductive graphite.

[0059] S5. The fully mixed materials are roll-pressed to form a low lithium loss active material layer.

[0060] Specifically, the low lithium loss active material is placed in a roller press and roller pressed at 20° C. to 120° C. and 3 MPa to 10 MPa to obtain a low lithium loss active material layer.

[0061] In some embodiments, the low lithium loss active material layer has a thickness of 20 μm to 120 μm.

[0062] S6. Forming a metal thin film by evaporating on the surface of the low lithium loss active material layer.

[0063] Specifically, the low lithium loss active material layer is placed in a vapor deposition machine, and a target material is vapor deposited on its surface to form a thin film, which is then sliced ​​to produce a dry-process lithium-silicon alloy negative electrode with high stability, low lithium loss, and high specific capacity. The thin film can be used as a conductive current collector for the negative electrode.

[0064] In some embodiments, the target material for evaporation is selected from any one of copper and aluminum; and the thickness of the metal film is 10 nm to 500 nm.

[0065] Some embodiments of the present invention further provide a lithium-ion battery, which includes a negative electrode prepared from the above-mentioned dry-process lithium-silicon alloy negative electrode material. That is, the above-mentioned dry-process lithium-silicon alloy negative electrode with high stability, low lithium loss and high specific capacity can be used as a negative electrode of a lithium-ion battery.

[0066] The features and performance of the present invention are further described in detail below in conjunction with the examples. The scanning electron microscope was a Zeiss Sigma Fesem and the ball mill was a Fritsch 20 Pulverisette.

[0067] Example 1

[0068] The present embodiment provides a lithium-silicon alloy nanoparticle and a dry-process lithium-silicon alloy negative electrode with high stability, low lithium loss and high specific capacity, and a preparation method thereof. The preparation of the lithium-silicon alloy nanoparticle and the dry-process lithium-silicon alloy negative electrode comprises the following steps:

[0069] 1)Reference Figure 2 At room temperature (5-30°C), 1 g of micron-sized lithium-silicon alloy powder 1 is weighed and added into a ball mill 2 for sealed ball milling. The powder is ground and pulverized at a ball milling speed of 400 rpm to obtain a lithium-silicon alloy core 3 with a particle size of ≤500 nm.

[0070] 2)Reference Figure 3 , 6 ml of tetrahydrofuran and 200 mg of acrylate functionalized high molecular fluorine-containing polymer were magnetically stirred at 100 rpm for 0.5 h, and after uniform mixing, the lithium silicon alloy core 3 in step 1 and 500 mg of diphenylacetone were added, and magnetically stirred at 200 rpm for 1.5 h. After sufficient mixing, ultraviolet light was irradiated for 10 min to obtain primary coated lithium silicon alloy nanoparticles 7.

[0071] 3)Reference Figure 4 , 6 ml of tetrahydrofuran and 200 mg of functionalized polyethylene glycol (average molecular weight of 600) were magnetically stirred at 100 rpm for 0.5 h. After uniform mixing, the lithium silicon alloy nanoparticles 7 coated once in step 2 and 500 mg of diphenylacetone were added and magnetically stirred at 200 rpm for 1.5 h. After thorough mixing, ultraviolet light was irradiated for 10 min. After drying, fully coated lithium silicon alloy nanoparticles 9 were obtained.

[0072] 4)Reference Figure 5 The fully coated lithium silicon alloy nanoparticles 9 obtained in step 3 and 100 mg of polytetrafluoroethylene, 100 mg of carbon nanotubes, 50 mg of polypropylene carbonate, and 100 mg of polyethylene glycol are placed in a mixer 10, and stirred and mixed at a speed of 150 rpm for 1 hour to obtain a low lithium loss active material 15.

[0073] 5)Reference Figure 6 The obtained low lithium loss active material 15 is placed in a roller press 16 and rolled to obtain a 100 μm thick low lithium loss active material layer 17 at 20° C. and 5 MPa.

[0074] 6)Reference Figure 7The low lithium loss active material layer 17 is placed in a vapor deposition machine 18, copper is vapor deposited on its surface to form a 50 nm thick uniform film, and after slicing, a dry-process lithium-silicon alloy negative electrode 20 with high stability, low lithium loss and high specific capacity is obtained.

[0075] Example 2

[0076] The only difference between this embodiment and embodiment 1 is that the ball milling speed in step 1 is 200 rpm.

[0077] Example 3

[0078] The only difference between this embodiment and embodiment 1 is that in step 2, 20 mL of tetrahydrofuran is mixed with 100 mg of acrylate functionalized high molecular weight fluorinated polymer.

[0079] Example 4

[0080] The only difference between this embodiment and embodiment 1 is that in step 3, 20 mL of tetrahydrofuran is mixed with 100 mg of functionalized polyethylene glycol.

[0081] Example 5

[0082] The only difference between this embodiment and the first embodiment is that in step 4, 500 mg of polytetrafluoroethylene, 500 mg of carbon nanotubes, 100 mg of polypropylene carbonate, and 500 mg of polyethylene glycol are mixed and stirred.

[0083] Example 6

[0084] The only difference between this embodiment and embodiment 1 is that the ball milling speed in step 4 is 450 rpm.

[0085] Example 7

[0086] The only difference between this embodiment and the first embodiment is that the evaporation target material in step 6 is aluminum.

[0087] Example 8

[0088] The only difference between this embodiment and the first embodiment is that the thickness of the evaporated film in step 6 is 500 nm.

[0089] Comparative Example 1

[0090] The difference between Comparative Example 1 and Example 1 is that there is no step 2 and step 3, and there is no stabilizer in step 4, and a conventional current collector is used in step 6, which specifically includes the following steps:

[0091] 1) At room temperature (5-30° C.), 1 g of micron-sized lithium-silicon alloy powder 1 is weighed and added to a ball mill 2 for sealed ball milling, and ground and pulverized at a ball milling speed of 400 rpm to obtain a lithium-silicon alloy core 3 with a particle size of ≤500 nm.

[0092] 2) The lithium silicon alloy nanocore 3 obtained in step 1, 11 mg of polytetrafluoroethylene and 11 mg of carbon nanotubes were placed in a mixer 10, and stirred and mixed at a speed of 150 rpm for 1 hour to obtain an active material.

[0093] 3) The obtained active material is placed in a roller press 16 and roller pressed at 20° C. and 5 MPa to obtain an active material layer 17 with a thickness of 100 μm.

[0094] 4) The active material layer 17 is rolled onto a 100 μm copper current collector coated with a conductive adhesive, and the lithium silicon alloy negative electrode is obtained after slicing.

[0095] Comparative Example 2

[0096] The difference between Comparative Example 2 and Example 1 is that there is no step 3, and specifically comprises the following steps:

[0097] 1) At room temperature (5-30° C.), 1 g of micron-sized lithium-silicon alloy powder 1 is weighed and added to a ball mill 2 for sealed ball milling, and ground and pulverized at a ball milling speed of 400 rpm to obtain a lithium-silicon alloy core 3 with a particle size of ≤500 nm.

[0098] 2) 6 ml of tetrahydrofuran and 200 mg of acrylate functionalized high molecular fluorine-containing polymer were magnetically stirred at 100 rpm for 0.5 h. After uniform mixing, the lithium silicon alloy nanoparticles 3 in step 1 and 500 mg of diphenylacetone were added, and magnetic stirring was performed at 200 rpm for 1.5 h. After sufficient mixing, ultraviolet light was irradiated for 10 min to obtain lithium silicon alloy nanoparticles 7.

[0099] 3) The lithium silicon alloy nanoparticles 7 obtained in step 2 and 100 mg of polytetrafluoroethylene, 100 mg of carbon nanotubes, 50 mg of polypropylene carbonate, and 100 mg of polyethylene glycol are placed in a mixer 10, and stirred and mixed at a speed of 150 rpm for 1 hour to obtain a low lithium loss active material 15.

[0100] 4) The obtained low lithium loss active material 15 is placed in a roller press 16 and roller pressed at 20° C. and 5 MPa to obtain a 100 μm thick low lithium loss active material layer 17 .

[0101] 5) The low lithium loss active material layer 17 is placed in a vapor deposition machine 18, copper is vapor deposited on its surface to form a 50 nm thick uniform film, and the lithium silicon alloy negative electrode 20 is obtained after slicing.

[0102] Comparative Example 3

[0103] The only difference between Comparative Example 3 and Example 1 is that no stabilizer is added in Step 4, that is, Step 4 is: placing the fully coated lithium silicon alloy nanoparticles 9 obtained in Step 3 and 100 mg of polytetrafluoroethylene, 100 mg of carbon nanotubes, 50 mg of polypropylene carbonate, and 100 mg of polyethylene glycol into a mixer 10, and stirring and mixing them at a speed of 150 rpm for 1 hour to obtain a low lithium loss active material 15.

[0104] Comparative Example 4

[0105] The only difference between Comparative Example 4 and Example 1 is that a conventional current collector is used in step 6, and step 5 is specifically: the active material layer 17 is rolled onto a 100 μm copper current collector coated with a conductive adhesive, and the lithium silicon alloy negative electrode is obtained after slicing.

[0106] Test example

[0107] The above-mentioned Examples 1-8 and Comparative Examples 1-4 were prepared into half-cells with metallic lithium foil as the negative electrode and the lithium silicon alloy electrode obtained in each Example and Comparative Example as the positive electrode for testing. The half-cell was a button-type 2032 battery, comprising a negative electrode shell, a spring, a gasket, a lithium foil, a diaphragm, a lithium silicon alloy electrode piece and a positive electrode shell. The electrolyte solute was 1 mol / L lithium hexafluorophosphate, the solvent was an EC-DEC solvent with a mass ratio of 1:1, and it also contained FEC with a mass fraction of 5%. The test was a constant current charge and discharge test, and the charge and discharge rate of the first cycle was 0.05C.

[0108] The test results are shown in Table 1.

[0109] Table 1 Performance parameters of battery tests for examples and comparative examples

[0110]

[0111]

[0112] As can be seen from Table 1, compared with other embodiments and comparative examples, Example 1 has a first coulombic efficiency of 137%, and a first discharge specific capacity of 2732 mAh / g, showing the best electrochemical performance. The lithium silicon alloy negative electrode (embodiment) prepared by the process flow described in the embodiment of the present invention has significantly excellent first coulombic efficiency and first discharge specific capacity compared with the lithium silicon alloy negative electrode (comparative example) prepared by the conventional process. The preparation process can be carried out in a conventional air environment, and at the same time has the advantage of less loss of lithium silicon alloy active substances.

[0113] The lithium-silicon alloy nanoparticles 9 fully coated with polymer secondary surface modification in Example 1 and the lithium-silicon alloy cores 3 without surface modification in Comparative Example 1 were observed by scanning electron microscope. The results are as follows: Figure 8 and Fig. 9 By comparison Figure 8 and Fig. 9 It can be seen that the lithium silicon alloy nanoparticles 9 are fully coated after surface polymerization by the macromolecular primary polymerizer and the small molecular secondary polymerizer, and a uniform and dense polymer coating layer is formed on the outer surface to block the reaction between the lithium silicon alloy and the external air.

[0114] In summary, the present invention utilizes the secondary reaction of the lithium-silicon alloy material (core) to form a lithium-silicon alloy material with a fully coated surface, thereby improving the stability of the lithium-silicon alloy material, reducing the equipment investment cost, and improving the economy; utilizing a stabilizer to supplement the polymer-free vacancies that appear after the wear of the lithium-silicon alloy surface coating layer, thereby preventing the reaction between the internal lithium and the water and oxygen in the external air, and reducing lithium loss; relying on the evaporation of a metal film on the surface of the low-lithium-loss active material layer containing the lithium-silicon alloy, conventional copper foil and aluminum foil are replaced to increase the electrode specific capacity and improve the electrode performance.

[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium silicon alloy nanoparticle, characterized in that: It includes a lithium silicon alloy core and a polymer layer located on the surface of the lithium silicon alloy core, wherein the polymer layer completely covers the lithium silicon alloy core, and the polymer layer includes a first coating layer obtained by polymerizing a perfluoropolymer with an average molecular weight greater than 5000 and a second coating layer obtained by polymerizing polyethylene glycol with an average molecular weight of 400-800, which sequentially cover the lithium silicon alloy core.

2. The lithium-silicon alloy nanoparticles according to claim 1, characterized in that: The chemical formula of the lithium silicon alloy core is Li x Si y , where x:y is 1:1~6:

1.

3. The lithium-silicon alloy nanoparticles according to claim 1, characterized in that: The particle size of the lithium silicon alloy core is 100nm~500nm.

4. The lithium-silicon alloy nanoparticles according to any one of claims 1 to 3, characterized in that: The components of the polymer layer include polyester compounds and polyethylene glycol compounds.

5. The method for preparing lithium-silicon alloy nanoparticles according to any one of claims 1 to 4, characterized in that: It includes: The polymer layer is generated by in-situ reaction on the surface of the lithium silicon alloy core.

6. The preparation method according to claim 5, characterized in that: The in-situ reaction to generate the polymer layer includes: subjecting the lithium silicon alloy core to a first polymerization coating through a primary polymerization agent, and then subjecting the lithium silicon alloy core to a second polymerization coating through a secondary polymerization agent, wherein the primary polymerization agent is a perfluoropolymer with an average molecular weight greater than 5000, and the secondary polymerization agent is polyethylene glycol with an average molecular weight of 400-800.

7. The preparation method according to claim 6, characterized in that: The first polymerization coating and the second polymerization coating are both ultraviolet light reaction polymerization initiated by a photoinitiator.

8. The preparation method according to claim 6, characterized in that: The primary polymerization agent is at least one of perfluoropolymers containing acrylate or methacrylate, and the secondary polymerization agent is polyethylene glycol containing acrylate or methacrylate.

9. The preparation method according to claim 6, characterized in that: The lithium silicon alloy core is obtained by ball milling lithium silicon alloy powder with a particle size of 100 μm to 500 μm.

10. The preparation method according to claim 6, characterized in that: The first polymerization coating of the lithium silicon alloy core by a primary polymerization agent comprises: placing the lithium silicon alloy core into a mixed solution containing the primary polymerization agent and a photoinitiator, and reacting by ultraviolet light irradiation.

11. The preparation method according to claim 10, characterized in that: The first polymerization coating time is at least 8 minutes.

12. The preparation method according to claim 10, characterized in that: The first polymerization coating time is at least 10 minutes.

13. The preparation method according to claim 10, characterized in that: The mass ratio of the lithium silicon alloy core, the primary polymerization agent, the photoinitiator and the solvent is (4.4-15): (0.1-2): (0.5-3): (80-95).

14. The preparation method according to claim 6, characterized in that: The second polymerization coating by the secondary polymerization agent includes: placing the lithium silicon alloy nanoparticles that have been firstly polymerized and coated into a mixed solution containing the secondary polymerization agent and a photoinitiator, and reacting by ultraviolet light irradiation.

15. The preparation method according to claim 14, characterized in that: The second polymerization coating time is at least 8 minutes.

16. The preparation method according to claim 14, characterized in that: The second polymerization coating time is at least 10 minutes.

17. The preparation method according to claim 14, characterized in that: The mass ratio of the lithium silicon alloy nanoparticles coated by the first polymerization, the secondary polymerization agent, the photoinitiator and the solvent is (4.3-15): (0.2-2): (0.5-3): (80-95).

18. The preparation method according to claim 6, characterized in that: The photoinitiators used in the first polymerization coating and the second polymerization coating both include at least one of diphenylacetophenone, α-hydroxyalkylphenone, bisbenzoylphenylphosphine oxide and benzophenone; the solvents used in the two coatings both include at least one of tetrahydrofuran, N-methylpyrrolidone and cyclohexane.

19. Use of the lithium-silicon alloy nanoparticles according to any one of claims 1 to 4 or the lithium-silicon alloy nanoparticles prepared by the preparation method according to any one of claims 5 to 18 in preparing a dry-process lithium-silicon alloy negative electrode.

20. A method for preparing a dry lithium-silicon alloy negative electrode material, characterized in that: It includes: The lithium silicon alloy nanoparticles, the binder, the additive, the conductive agent and the stabilizer are fully mixed; Wherein, the lithium-silicon alloy nanoparticles are the lithium-silicon alloy nanoparticles according to any one of claims 1 to 4 or the lithium-silicon alloy nanoparticles prepared by the preparation method according to any one of claims 5 to 18, and the stabilizer is a substance that can react on the surface of the lithium-silicon alloy nanoparticles to form lithium-oxygen bonds; The additive comprises at least one of polypropylene carbonate, polytrimethylene carbonate and polycyclohexene carbonate; The stabilizer includes at least one of polyethylene glycols with different molecular weights.

21. The preparation method according to claim 20, characterized in that: The mass ratio of the lithium silicon alloy nanoparticles, the binder, the additive, the conductive agent and the stabilizer is: (30~95): (1~35): (1~15): (1~5): (2~15).

22. The preparation method according to claim 20, characterized in that: The binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyethylene oxide, sodium hydroxymethyl cellulose, styrene-butadiene rubber, polyethylene, polypropylene and polyacrylonitrile; the conductive agent includes at least one of composite conductive agent SP, carbon nanotubes, nano-carbon fibers, Ketjen black and conductive graphite.

23. The preparation method according to claim 20, characterized in that: The dry process lithium-silicon alloy negative electrode material preparation method further includes rolling the fully mixed materials to form a low lithium loss active material layer.

24. The preparation method according to claim 23, characterized in that: The method also includes using the low lithium loss active material layer as a substrate and vapor-depositing a metal film on the surface of the substrate.

25. The preparation method according to claim 24, characterized in that: The target material for evaporation is selected from either copper or aluminum.

26. The preparation method according to claim 24, characterized in that: The thickness of the metal film is 10nm~500nm.

27. A lithium ion battery, characterized in that: It includes a negative electrode prepared by the dry process lithium-silicon alloy negative electrode material preparation method as described in any one of claims 20 to 26.

Citation Information

Patent Citations

  • Lithium silicon alloy material with surface modification layer, preparation method thereof, electrode and electrochemical energy storage device and negative electrode lithium-supplementing method

    CN108565414A

  • Encapsulated anode active material particles, lithium secondary batteries containing same, and method of manufacturing

    CN110663129A

Cited By

  • Preparation method and application of nanoscale lithium-silicon alloy

    CN121156290A

  • A method for preparing nanoscale lithium-silicon alloy and its application

    CN121156290B